Time Clustered Sampling Can Inflate the Inferred Substitution Rate in Foot-And- Mouth Disease Virus Analyses - Pedersen, Casper-Emil T.; Frandsen, Peter; Wekesa, Sabenzia N.; Heller, Rasmus; Sangula, Abraham K.; Wadsworth, Jemma; Knowles, Nick J.; Muwanika, Vincent B.; Siegismund, Hans R. (PLoS ONE, 2015)
With the emergence of analytical software for the inference of viral evolution, a number of studies have focused on estimating important parameters such as the substitution rate and the time to the most recent common ancestor (tMRCA) for rapidly evolving viruses. Coupled with an increasing abundance of sequence data sampled under widely different schemes, an effort to keep results consistent and comparable is needed. This study emphasizes commonly disregarded problems in the inference of evolutionary rates in viral sequence data when sampling is unevenly distributed on a temporal scale through a study of the foot-andmouth (FMD) disease virus serotypes SAT 1 and SAT 2. Our study shows that clustered temporal sampling in phylogenetic analyses of FMD viruses will strongly bias the inferences of substitution rates and tMRCA because the inferred rates in such data sets reflect a rate closer to the mutation rate rather than the substitution rate. Estimating evolutionary parameters from viral sequences should be performed with due consideration of the differences in short-term and longer-term evolutionary processes occurring within sets of temporally sampled viruses, and studies should carefully consider how samples are combined.
Keywords: Foot-And- Mouth Disease; Virus Analyses